Developing Instructional Media Based on ICT for Fourth Grade Students - Nurul Afidah; Oktavia Ayu Kristanti; Hanifah Hanifah (SCHOOLAR: Social and Literature Study in Education, 2022)
ABSTRACT The aim of this study is to develop ‘English Fun’ in English instruction for fourth grade students of MI Al Hidayah Pagotan Jombang. This product focused on some vocabularies such as fruit, part of body, vegetables, and animals. The researcher chooses the ADDIE model in developing the product. This model consists of five steps. Those are: (1) analyze, (2) design, (3) development, (4) implementation, and (5) evaluation.on develop phase, validation sheet was used to evaluate the quality of English Fun that was developed. Based on the data from the material expert validation sheet instrument above, the average of the overall aspect was 94% which means this product was “very good" and deserves to be implemented. The following were the validation results from media experts. Based on the data from the media expert validation sheet instrument above, the average of the whole aspect was 89% which mean this product was “very good” and feasible to be implemented. Based on the results of implementation with 10 students as a respondent, the result was 67% which mean that the results of the implementation were included in "good" which mean this instructional media can be used as a means of learning media to help students in learning activities